2019
DOI: 10.3390/min9120759
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Distribution in Magnetite Separates of Varying Origin: Genetic and Exploration Significance

Abstract: Magnetite is a widespread mineral, as disseminated or massive ore. Representative magnetite samples separated from various geotectonic settings and rock-types, such as calc-alkaline and ophiolitic rocks, porphyry-Cu deposit, skarn-type, ultramafic lavas, black coastal sands, and metamorphosed Fe–Ni-laterites deposits, were investigated using SEM/EDS and ICP-MS analysis. The aim of this study was to establish potential relationships between composition, physico/chemical conditions, magnetite origin, and explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 68 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…The authors applying thermodynamic modelling of fluid-rock interactions concluded that fractionation processes such as phase separation were critical to generate hydrothermal fluids capable of precipitating large amounts of magnetite in various types of ultramafic host rocks [8]. Although variable textures described in the large Cogne magnetite deposit differ from those in the Pindos magnetite ore, the trace element content of magnetite from the Cogne deposit, characterized by high Mg and Mn and low Cr, Ti, and V [8], is comparable to those in the Pindos magnetite separates [57]. Additionally, Fe-Cu-Zn-Co-Ni mineralization has been reported in seafloor VMS deposits from modern oceans, as well as in their potential analogues on several ophiolite complexes, as exemplified in the Urals, supporting the origin of such deposits by hydrothermal processes [19].…”
Section: A Comparison Between Magmatic Sulphides and Those Hosted In mentioning
confidence: 99%
“…The authors applying thermodynamic modelling of fluid-rock interactions concluded that fractionation processes such as phase separation were critical to generate hydrothermal fluids capable of precipitating large amounts of magnetite in various types of ultramafic host rocks [8]. Although variable textures described in the large Cogne magnetite deposit differ from those in the Pindos magnetite ore, the trace element content of magnetite from the Cogne deposit, characterized by high Mg and Mn and low Cr, Ti, and V [8], is comparable to those in the Pindos magnetite separates [57]. Additionally, Fe-Cu-Zn-Co-Ni mineralization has been reported in seafloor VMS deposits from modern oceans, as well as in their potential analogues on several ophiolite complexes, as exemplified in the Urals, supporting the origin of such deposits by hydrothermal processes [19].…”
Section: A Comparison Between Magmatic Sulphides and Those Hosted In mentioning
confidence: 99%
“…Such is the situation at the Bapy ore deposit in Kazakhstan. The lack of efficient industrial-grade machines and apparatus for separating fine-grained magnetite ores means that DMS is used mainly as a pre-concentration operation for fairly large classes (Duman et al, 2019;Chang and Cheng, 2019;Fan et al, 2019;Eliopoulos and Economou-Eliopoulos, 2019). Thus, at the Bapy deposit, the -10mm grade ore is brought to an iron concentration of 52-54% by means of DMS, using traditional drum separators.…”
Section: Introductionmentioning
confidence: 99%